Investment versus economic development - Janicki, Tadeusz (Studia Historiae Oeconomicae, 2025)
Physical and human capital investments are considered one of the most important factors for economic growth, regardless of the historical era. their history and role in economic life are still under-researched from the viewpoint of economic history. Especially since knowledge of the different aspects and dimensions of investment, the links between investment and changes in the economy, as well as the results of investment, is one of the prerequisites for knowing and explaining the processes of regional, national and international economic development or regression, and for effective economic policies. the studies contained in the next volume of the journal Studia historiae oeconomicae analyze the above problem using selected examples dating back to the 18th century. They provide original insights into state and local government investment, other phenomena, and problems concerning this element of economic life. in addition to six articles on historical issues, the current volume in the materials and methods section contains three articles of a methodological and theoretical nature on methods of land use and land cover research using the specialized software SAS Studio, the development of a universal bankruptcy prediction model for listed non-financial firms, and the role of digital humanities and its potential in contemporary educational processes.